2020
DOI: 10.1016/j.neuroimage.2019.116486
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to localize cortical TMS effects

Abstract: 21 22 1 METHODS 24 1.1 Determining the site of stimulation 25In the following, the two approaches to determine the congruence factor are presented. The site of effective stimulation 26 is determined by combining the measured I/O-curves of the MEP amplitude with the simulation results of the induced 27 electric field. An operator is derived to transform the brain-wide MEP amplitude curves with 1, … , 28indicating the experimental condition, given as a function of stimulator intensities x, to an element-wise qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 71 publications
3
140
0
Order By: Relevance
“…This also applies to the precentral gyrus hosting the motor hand representation. The preferential site of direct TMS-induced excitation is the crown-and-lip region, because the electrical field strength is highest in this most superficial part of the precentral gyrus (8)(9)(10). Cytoarchitectonic mapping studies showed that the rostral border of the primary motor cortex is located at the surface of the precentral crown close to the midline, but disappears in the rostral bank of the central sulcus in more lateral parts of the hemisphere (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…This also applies to the precentral gyrus hosting the motor hand representation. The preferential site of direct TMS-induced excitation is the crown-and-lip region, because the electrical field strength is highest in this most superficial part of the precentral gyrus (8)(9)(10). Cytoarchitectonic mapping studies showed that the rostral border of the primary motor cortex is located at the surface of the precentral crown close to the midline, but disappears in the rostral bank of the central sulcus in more lateral parts of the hemisphere (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The individually calculated mean EF strength in the motor cortex significantly correlated with the measured RMT (R 2 = 0.44). Weise et al (2020) performed motor-cortical-based TMS measurements using several coil locations and orientations in 15 subjects and modelled the induced EFs using MRIbased head models. By investigating the congruence of the calculated EF and the measured MEP amplitudes, the authors showed that the origin of MEPs was around the gyral crowns and upper parts of the sulcal wall, and that the EF strength was the most relevant quantity to explain the observed effects.…”
Section: Tms Localisation and Validationmentioning
confidence: 99%
“…For the past 30 years, computational dosimetry has progressed significantly in biophysical and electrophysiological modelling techniques to investigate the effects of electromagnetic fields in the human body. In TMS, the primary physical agent known to activate neurons is the induced electric field (EF); moreover, recent studies have enabled the prediction of the stimulation location and optimised the dosages of the stimulation parameters (Opitz et al, 2014;Aonuma et al, 2018;Seynaeve et al, 2019;Weise et al, 2020). These procedures estimate the EF in the brain while considering the effects of the various physical aspects involved in TMS (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We compared results obtained by directly computing 〈‖ ( )‖〉 with ones for ‖〈 ( )〉‖ for ROIs of varying sizes to assess the accuracy of this approximation. Furthermore, we ran SimNIBS [47] coil placement optimization to maximize 〈‖ ( )‖〉 and compared with our results obtained by maximizing ‖〈 ( )〉‖. This was accomplished within SimNIBS by co-registering the diffusion-weighted imaging data employing a volume normalization of the brain conductivity tensor, where the geometric mean of the tensor eigenvalues was set to the default isotropic conductivities of 0.275 and 0.126 S/m for gray and white matter, respectively.…”
Section: Simultaneously Optimizing Coil Placement and E-field Directionmentioning
confidence: 99%